Research and Application of Online Sampling Technology for Mercury and CO2 in Flue Gas Emission Continuous Monitoring Systems of Thermal Power Plants - Wang Zhiliang (Return : Study of Management, Economic and Bussines, 2025)
Monitoring  emissions  in  thermal  power  plants  requires  high-accuracy and real-reliability systems, particularly for critical pollutants such as mercury (Hg) and carbon dioxide (CO2). Conventional manual sampling often faces limitations in response  speed,  data  continuity,  and  representativeness,  creating  challenges  for compliance with increasingly strict environmental regulations. This research aims to  analyze  the  design,  performance,  and  field  application  feasibility  of  an  online sampling technology integrated within Continuous Emission Monitoring Systems (CEMS) specifically for Hg and CO2 in flue gas. The methodology includes a technical  evaluation  of  sampling  modules,  assessment  of  sensor  accuracy  and stability, calibration and validation using reference methods, and on-site testing in a  coal-fired  thermal  power  plant.  Data  were  analyzed  through  comparative measurements, response time analysis, and long-term operational reliability testing. Results    indicate    that    online    sampling    technology    significantly    improves measurement   continuity   and   reduces   data   fluctuation   compared   to   manual sampling.  The  system  demonstrates  high  accuracy,  with  CO2  measurement deviations within regulatory thresholds and mercury detection sensitivity enhanced through optimized temperature-controlled sampling lines. Additionally, technology reduces   maintenance   frequency   by   minimizing   condensation   and   particulate interference,  thereby  increasing  system  uptime.  Overall,  the  online  sampling approach  offers  a  more  stable  and  efficient  solutionfor  emission  monitoring  and supports  the  implementation  of  stricter  environmental  compliance  strategies  in thermal power plants